Short term money markets - Griffiths, Nigel; Smith, Warren F. (London : Euromoney Publications PLC, 1990)
Pre films illustrate the interrelationship between various forms of debt financing that makes it possible to consider the existence of the world's money markets, examine the trading environment and explain the market's importance for central government and monetary policy
' Filmed on location at the Union Discount Company of London'
' Sponsored by the Union Discount Company'
Copy available in DVD format
Keywords: Money market